THE READING OF NEW TESTAMENT BIBLE MANUSCRIPTS IN THE BYZANTINE TEXT - Simanjuntak, Ferry; Suwandi, Markus; A. Usmanij, Petrus (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT This article aims to apply intertextual reading in the science of hermeneutical exegesis, especially in the New Testament (NT) which are narrative in nature. The messages of the Bible are often misunderstood because readers only rely on translations that are inadequate and lack the depth of meaning of the original text. Hebrew is one of three languages along with Aramaic, and Koine Greek in which God chose to communicate His Word. Reading the New Testament in its original text will reveal a deeper meaning than the translated version. This paper uses a descriptive qualitative method approach with literature study as the main method. The original text analyzed is the canonical text of the Byzantine NT. Through a hermeneutic approach, this text is read to understand and comprehend theological messages in a comprehendsive perspective. The results of this study conclude that reading the original text of the New Testament provides a more contextual and applicable theological understanding and understandding related to Christian doctrine. Keywords: Bizantine Text, Canon, Koine Greek, Manuscript, New Testament. ABSTRAK Tujuan artikel ini menerapkan pembacaan intertektualitas dalam ilmu eksegese hermeneutika, khususnya pada genre teks di Perjanjian Baru (PB) yang bersifat naratif. Pesan-pesan Alkitab seringkali disalahpahami karena pembaca hanya mengandalkan terjemahan yang kurang mencukupi dan memiliki kedalaman makna dari teks aslinya. Bahasa Ibrani adalah salah satu dari tiga bahasa bersama Aram, dan Yunani Koine di mana Allah memilih untuk mengkomunikasikan Firman-Nya. Pembacaan Kitab PB dalam teks originalnya akan mengungkapkan makna mendalam yang Allah ungkapkan pada pembaca dalam konteks saat ini. Tulisan ini menggunakan pendekatan metode kualitatif deskriptif dengan studi literatur sebagai basis datanya. Teks original yang dianalisa adalah teks Byzantine PB yang kanon. Melalui pendekatan hermeneutic, teks ini dibaca untuk mengerti dan memahami pesan-pesan teologis dalam perspektif yang benar. Hasil penelitian ini menyimpulkan bahwa pembacaan teks original PB menghasilkan pengertian, dan pemahaman teologis yang lebih kontekstual serta aplikatif terkait dengan doktrin Kristen. Kata Kunci: Kanon, Manuskrip, Perjanjian Baru, Teks Byzantium, Yunani Koine,